Efficacy of Parenteral Cefotaxime Versus Combination of Piperacillin & Tazobactam as Empiric First Line Therapy in the Treatment of Spontaneous Bacterial Peritonitis - Khanal, Ajit; Mishra, Anil Kumar (Journal of Society of Surgeons of Nepal, 2025)
Introduction: Cefotaxime is the empiric antibiotic of choice for spontaneous bacterial peritonitis (SBP). However, rising gram-positive pathogen rates have prompted consideration of piperacillin-tazobactam as an alternative. This study compares their efficacy in treating SBP among cirrhotic patients. Methods: Thirty hospitalized cirrhotic patients diagnosed with SBP (ascitic fluid neutrophils > 250/mm3) were randomized into two groups: 15 received cefotaxime (2g IV twice daily), and 15 received Piperacilin-Tazobactam (4.5 g IV every eight hours), both for five days. More than 25% reduction in neutrophil count after 48 hours defined treatment response. Results: The response rate was 60% (9/15) in the cefotaxime group vs. 93.3% (14/15) in the piperacillin-tazobactam group (p=0.084). Among patients with prior SBP on quinolone prophylaxis, 75% receiving cefotaxime failed to respond, while 80% receiving Piperacillin-Tazobactam responded. Conclusion: Piperacillin/Tazobactam is as effective as Cefotaxime and may be superior in patients with prior SBP episodes on prophylaxis. These common clinical scenarios suggest Piperacillin-Tazobactam could be a more suitable empiric first line therapy for SBP in cirrhotic patients.